KEBIJAKAN INDONESIA DALAM MENOLAK IMPOR SAPI BRAZIL TAHUN 2009-2014 - Yona Princy; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Indonesia's demand for beef keeps growing and causes the increasing gap between its low national bovine production and high consumption scale. This matter leads Indonesia to importing bovine from other countries. Brazil as one of the bovine’s export country has asks Indonesia to open its market for Brazil’s bovine product. Indonesia has its own regulation for international trade and Brazil is not comply the cattle’s health standart of Indonesia for exporting their bovine and bovine meat product..This research theoretically has built by using Heckscher – Ohlin theory and merchantilism point of view. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using nation-state as the level of analyze, the focus on this research is explain the causes of the rejection of Brazil’s Bovine Import according to Indonesia’s international trade policy.This research proves that the health standart of importing in Indonesia is a main factor for its international trade policy. Reseacrher has formulated the hypothesis answer which proved that the Indonesia’s health standard of cattle importing have the main effect in Indonesia’s rejection of Brazil’s bovine import.Keywords : Bovine selfsupporting program, Cattle ‘s health standar, Heckscher-Ohlin theory, International trade policy, Merchantilism point of view